2020
DOI: 10.3390/ijms21176305
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Zinc Oxide Nanostructures with Mammalian Cells: Cytotoxicity and Photocatalytic Toxicity

Abstract: This article presents a state-of-the-art review and analysis of literature studies on the morphological structure, fabrication, cytotoxicity, and photocatalytic toxicity of zinc oxide nanostructures (nZnO) of mammalian cells. nZnO with different morphologies, e.g., quantum dots, nanoparticles, nanorods, and nanotetrapods are toxic to a wide variety of mammalian cell lines due to in vitro cell–material interactions. Several mechanisms responsible for in vitro cytotoxicity have been proposed. These include the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 200 publications
(432 reference statements)
1
55
0
Order By: Relevance
“…Our main object of the studies was core-shell (cadmium selenide and zinc sulfide, respectively) quantum dot nanoparticles, synthesized and exploited industrially mainly due to their quantum state-related optical and electronic properties. Their physico-chemical characteristics which were most relevant to our study are their relatively small size (average diameter 6.2 nm), allowing for their potentially efficient cellular uptake both by triggered endocytosis and more passively by macropinocytosis [ 22 , 23 ]; poly-anionic carboxyl group surface modification, providing potential mechanisms of escape to cytoplasm [ 24 ]; and adsorptive interactions with important cellular components, including proteins [ 25 ] and mitochondrial lipids [ 26 ]; and the inclusion of two heavy metal elements in their structure, cadmium (in the core) and zinc (in the shell), which both have a plethora of known toxicological effects when in the form of free ions [ 27 ]. These QDs have a broad technological and biotechnological application range, extensively reviewed in [ 28 ], encompassing transistor and semiconductor nanoelectronics fabrication, production of lasers, solar cells and light-emitting diodes, medical imaging, and drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Our main object of the studies was core-shell (cadmium selenide and zinc sulfide, respectively) quantum dot nanoparticles, synthesized and exploited industrially mainly due to their quantum state-related optical and electronic properties. Their physico-chemical characteristics which were most relevant to our study are their relatively small size (average diameter 6.2 nm), allowing for their potentially efficient cellular uptake both by triggered endocytosis and more passively by macropinocytosis [ 22 , 23 ]; poly-anionic carboxyl group surface modification, providing potential mechanisms of escape to cytoplasm [ 24 ]; and adsorptive interactions with important cellular components, including proteins [ 25 ] and mitochondrial lipids [ 26 ]; and the inclusion of two heavy metal elements in their structure, cadmium (in the core) and zinc (in the shell), which both have a plethora of known toxicological effects when in the form of free ions [ 27 ]. These QDs have a broad technological and biotechnological application range, extensively reviewed in [ 28 ], encompassing transistor and semiconductor nanoelectronics fabrication, production of lasers, solar cells and light-emitting diodes, medical imaging, and drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…ZnO NPs are partially soluble to release Zn ions (J. Liu et al, 2016). Indeed, extensive studies suggested that ZnO‐based NPs induced cytotoxicity by inducing excessive intracellular Zn ions due to the dissolution of ZnO (Gong, Ji, Liu, Li, & Cao, 2017; Liao, Jin, Li, & Tjong, 2020; Yan et al, 2019). Consistently, here, we found that Ag/ZnO, Ag@ZnO, and ZnO NPs only significantly promoted intracellular Zn ions at cytotoxic concentrations (Figure S3), which indicated a role of excessive Zn ions in cytotoxicity of NPs.…”
Section: Discussionmentioning
confidence: 99%
“…They further react as explained in the following reactions to generate the reactive species. These active species further interact with the dye molecules and degradation of malachite green is carried out [47][48][49].…”
Section: Photocatalytic Dye Degradation By Doped and Undoped Bivo 4 Powdersmentioning
confidence: 99%